Students’ Stress Coping Mechanism - E. Kristanti; Dominifridus Bone; Helidorus Anin (Research Collaboration Community (RCC), 2024)
Academic stress is often found in students and is sometimes difficult to avoid. Stressful conditions often have a negative impact on students' mental health. For this sake, adaptive coping strategies are needed. This present study aims at: (1) describing the level of family resilience; academic self-efficacy; stress coping mechanisms; (2) analyzing the influence of family resilience and academic self-efficacy on stress coping mechanisms. Questionnaires were used as the instrument of this study and multiple regression techniques were applied as the techniques for data analysis. The result revealed that family resilience has a significant effect on stress coping mechanisms (Sig. 0.047 < 0.05), academic self-efficacy has a significant effect on stress coping mechanisms (Sig. 0.005 < 0.05). The effective contribution is 21.58%, family resilience and academic self-efficacy have a significant effect on stress coping mechanisms. Meanwhile, the relative contribution of family resilience to stress coping mechanisms is 38.6%, academic self-efficacy to stress coping mechanisms is 61.4%. Academic self-efficacy has a stronger influence on stress coping mechanisms. In this way, families are expected to increase their family's resilience, students are expected to increase their academic self-efficacy so that they have good stress coping mechanisms and are adaptive in dealing with their academic problems.